Keputusan Pembelian Ulang Ditinjau Dari Citra Merek, Media Iklan, dan Brand Trust Pada Produk Imboost Di Surakarta - Mahartiwi Kusuma Wardhani; Sudarwati Sudarwati; Ida Aryati; Sitti Mukarromah (ITB AAS INDONESIA Surakarta, 2021)
This study aims to examine the effect of Brand Image, Advertising Media, and Brand Trust on repurchase decisions. The population in this study is an infinite number of consumers in Surakarta. The sampling technique in this study used purposive sampling which resulted in a sample of 100 respondents. The data used in this study are primary data collected by filling out questionnaires. The results of this study indicate that Brand Image has a positive and significant effect on repurchase decisions, Advertising Media has a positive and significant effect on repurchase decisions, and Brand Trust has a positive and significant effect on repurchase decisions. Keywords: Brand Image, Advertising Media, and Brand Trust